Agroecological Initiative Project. Individual report on vision to action for Senegal - Piraux, Marc (2023)
The aim of this report is to analyse the methods and results obtained in relation to the visioning, development of transition pathways and work plans at the ALL in the department of Fatick in Senegal. The latter was chosen because it corresponds to the scale of action of the DYTAEL on the one hand, but also because it was the cradle of the activities of an EU Desira project, called FAIRSAHEL, which has made it possible since the end of 2021 to consolidate thinking on the AE transition in the territory. The report also covers the activities carried out under the EI Initiative since March of this year. There have been many original activities.